Teacher communication model with deaf junior high school students in mathematics learning at SLBN Sukamaju - Purna Bayu Nugroho; Manmeet Kaur (Universitas Muhammadiyah Lampung, 2026)
The purpose of this study was to determine the communication model of teachers with deaf junior high school students in mathematics learning at SLBN Sukamaju. This study is a qualitative descriptive study. The subjects of this study were teachers and deaf students at SLBN Sukamaju. The research subjects were selected using a purposive sampling technique. The data in this study were the results of observations using observation sheets and interview recordings. Data collection was carried out by conducting classroom observations, recording interviews, and writing down necessary notes. The collected data were then reduced. Data reduction was carried out simultaneously with data triangulation. The results of this study concluded that the communication model of teachers with deaf students is a top-down question model. The teacher starts the conversation with a question. Before the teacher explains the material, the teacher asks about the student's condition. Before the teacher asks the student to answer the question, the teacher asks about the student's personal life to ensure that the student returns to focus on learning. This communication model is a two-way communication model that provides opportunities for students to respond and ask questions regarding things they do not understand.